Complications in patients with cardiogenic shock on veno-arterial extracorporeal membrane oxygenation therapy: distribution and relevance. Results from an international, multicentre cohort study - Beer, Benedikt Norbert; Kellner, Caroline; Goßling, Alina; Sundermeyer, Jonas; Besch, Lisa; Dettling, Angela Deborah; Kirchhof, Paulus; Blankenberg, Stefan; Bernhardt, Alexander; Brunner, Stefan; Colson, Pascal; Eckner, Dennis; et al. (European heart journal - acute cardiovascular care, 2023)
Veno-arterial extracorporeal membrane oxygenation therapy (VA-ECMO) restores circulation and tissue oxygenation in cardiogenic shock (CS) patients, but can also lead to complications. This study aimed to quantify VA-ECMO complications and analyse their association with overall survival as well as favourable neurological outcome (cerebral performance categories 1 + 2).All-comer patients with CS treated with VA-ECMO were retrospectively enrolled from 16 centres in four countries (2005-2019). Neurological, bleeding, and ischaemic adverse events (AEs) were considered. From these, typical VA-ECMO complications were identified and analysed separately as device-related complications. n = 501. Overall, 118 were women (24%), median age was 56.0 years, median lactate was 8.1 mmol/L. Acute myocardial infarction caused CS in 289 patients (58%). Thirty-days mortality was 40% (198/501 patients). At least one device-related complication occurred in 252/486 (52%) patients, neurological AEs in 108/469 (23%), bleeding in 192/480 (40%), ischaemic AEs in 123/478 (26%). The 22% of patients with the most AEs accounted for 50% of all AEs. All types of AEs were associated with a worse prognosis. Aside from neurological ones, all AEs and device-related complications were more likely to occur in women; although prediction of AEs outside of neurological AEs was generally poor.Therapy and device-related complications occur in half of all patients treated with VA-ECMO and are associated with a worse prognosis. They accumulate in some patients, especially in women. Aside from neurological events, identification of patients at risk is difficult, highlighting the need to establish additional quantitative markers of complication risk to guide VA-ECMO treatment in CS.
Gesehen am 08.07.2024